Transdiagnostic Cognitive-Behavioral Therapy for Depression and Anxiety Disorders in Cardiovascular Disease Patients: Results From the CHAMPS Pilot-Feasibility Trial - Tully, Phillip J.; Turnbull, Deborah A.; Horowitz, John D.; Beltrame, John F.; Baune, Bernhard T.; Sauer-Zavala, Shannon; Baumeister, Harald; Bean, Christopher G.; Pinto, Ronette B.; Cosh, Suzie; Wittert, Gary A. (Frontiers in Psychiatry, 2022)
Objective: The aim of the Cardiovascular Health in Anxiety and Mood Problems Study (CHAMPS) is to pilot the Unified Protocol (UP) for the transdiagnostic treatment of depression and anxiety disorders in patients recently hospitalized for cardiovascular diseases (CVDs) and evaluate the feasibility. Methods: The present study is a controlled, block randomized pragmatic pilot-feasibility trial incorporating qualitative interview data, comparing UP (n=9) with enhanced usual care (EUC, n=10). Eligible trial participants had a recent CVD-cause admission and were above the severity threshold for depression or anxiety denoted by Patient Health Questionnaire (PHQ-9) total scores ≥ 10 and/or Generalized Anxiety Disorder (GAD-7) total scores ≥ 7 respectively on two occasions, and met criteria for one or more depression or anxiety disorders determined by structured clinical interview. Study outcomes were analyzed as intention-to-treat using linear mixed models and qualitative interview data were analyzed with content analysis. Results: Quantitative and qualitative measured indicated acceptability of the transdiagnostic CBT intervention for CVD patients with depression or anxiety disorders. Satisfaction with UP was comparable to antidepressant therapy and higher than general physician counseling. However, there were difficulties recruiting participants with current disorders and distress on two occasions. The UP was associated with a reduction in total number of disorders determined by blinded raters. Linear mixed models indicated that a significantly greater reduction in anxiety symptoms was evident in the UP group by comparison to the EUC group (GAD-7, p between groups = 0.011; Overall Anxiety Severity and Impairment Scale, p between groups = 0.013). Results favored the UP group by comparison to EUC for change over six months on measures of physical quality of life and harmful alcohol use. There was no difference between the two groups on changes in depression symptoms (PHQ-9), stress, metacognitive worry beliefs, physical activity, or adherence. Discussion: In conclusion, our feasibility trial indicates acceptability of transdiagnostic CBT intervention for CVD patients with depression or anxiety disorders that is tempered by difficulties with recruitment. Larger trials are required to clarify the efficacy of transdiagnostic depression and anxiety disorder CBT in populations with CVDs and depressive or anxiety disorders. Registration: ACTRN12615000555550